A Systematic Review of Experimental Approaches on Public Service Motivation - Chung, Kee Hoon; Rhee, Inbok; Liu, Cheol (KDI School of Public Policy and Management, 2021)
Recent studies on public service motivation (PSM) have increasingly adopted experimental approaches. This article provides a systematic review of the existing experimental studies on PSM and suggests guidance for future research. We assess the existing literature based on two criteria that differentiate experimental methods from observational ones: whether PSM is measured through an experiment and whether the research design operates treatment intervention for PSM. After reviewing a sample of 26 published studies, we find that only one study met both criteria. Most studies measure PSM through a self-reported survey and lack treatment effects, making it difficult to differentiate them from observational studies. Furthermore, external validity remains a concern, as most studies use students as proxies for civil servants or focus only on Western states. We conclude that experimental studies on PSM remain at a nascent stage with much room for improvement, especially the experimental design.